High Performer Peer Effects: A Review, Synthesis, and Agenda for Future Research. (July 2023) - Hendricks, Jonathan L.; Call, Matthew L.; Campbell, Elizabeth M.
For decades, scholars and managers alike have shared a sustained interest in harnessing the talents of high-performing employees primarily due to their disproportionate contributions. An emerging research stream has begun examining the diverse effects that high performers elicit on their peers. Prior work now spans multiple organizational fields of study and utilizes a variety of high performer conceptualizations, theoretical lenses, and methodological approaches to examine the main effects of high performers as well as the boundary conditions of these effects. However, the body of work on high performers has yet to be systematically reviewed to synthesize the current state of the high performer literature and build commonality across disciplines. In this multidisciplinary review, we first establish conceptual clarity on what a high performer is (and is not) and identify the conceptualization of high performers used in current research. We then use appraisal theories to create a framework to organize the cognitive, affective, and behavioral peer effects sparked by high performers as well as to build an integrative view of the psychological mechanisms through which peers interpret and react to high performers. Following this, we outline several boundary conditions of high performer peer effects, including the characteristics of high performers, peers, and the context in which high performers and peers interact. We further consider how the various operationalizations of high performers are associated with different peer effects. We conclude by identifying and elaborating several avenues for future research that may yield useful cross-disciplinary insights.